Behaviour Management : A Whole-School Approach - Rogers, Bill (Paul Chapman Publishing, 2007)
In this revised and updated edition of Bill Rogers verselling book, the author draws on his extensive experience as an educational consultant and trainer to help teachers and managers develop a whole school strategy for dealing with student behaviour. In this distinctive accesible and entertaining style, he offers practical suggestions to support teachers as they face the pressures of accountability, assessmenr and rising concerns about student behaviour.